(3eONd eJcGeds - (3jhSa MLje SdWGf(B, (3GdWGFjs; (3YGeQ Ydj MSjf GdYWhj(B, s ((3YeGf(B:s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B,s, 2010)
(3fTCI GdPcGA GdTYhQj, eQGMd JWhQg h ejGOjf OQGSJg h GdWHjYI GdYVhjI dg, GdPcGA GdTchQj ddaQO h NUGFU eQJaYj h efNaVj GdPcGA GdTYhQj, feGPL h ebGjjS GdPcGA GdTYhQj ddaQO, feGPL h ebGjjS GdPcGA GdTYhQj ddaQjb h JWhQ gPG GdPcGA aj GdefXeI h CNjQG GdPcGA GdTYhQj ddbGFOs
Keywords: (3GdPcGAs; (3GdSdhc GdEOGQjs; (3Yde GdfaS GdJWHjbjs